2011
DOI: 10.1073/pnas.1108472108
|View full text |Cite
|
Sign up to set email alerts
|

The aneurogenic limb identifies developmental cell interactions underlying vertebrate limb regeneration

Abstract: The removal of the neural tube in salamander embryos allows the development of nerve-free aneurogenic limbs. Limb regeneration is normally nerve-dependent, but the aneurogenic limb regenerates without nerves and becomes nerve-dependent after innervation. The molecular basis for these tissue interactions is unclear. Anterior Gradient (AG) protein, previously shown to rescue regeneration of denervated limbs and to act as a growth factor for cultured limb blastemal cells, is expressed throughout the larval limb e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 40 publications
(54 reference statements)
1
37
0
Order By: Relevance
“…AREG and CDX2 expression thus provided an opportunity to evaluate the protein domains necessary for AGR2 function. Published studies to date have reported an extracellular role for AGR2 as a secreted protein as well as an intracellular role as a protein chaperone or stress response factor (7,10,14,16,32,33). Among the factors favoring an intracellular role based in the ER is the presence of a carboxyl-terminal motif, KTEL, that is conserved from Xenopus to humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AREG and CDX2 expression thus provided an opportunity to evaluate the protein domains necessary for AGR2 function. Published studies to date have reported an extracellular role for AGR2 as a secreted protein as well as an intracellular role as a protein chaperone or stress response factor (7,10,14,16,32,33). Among the factors favoring an intracellular role based in the ER is the presence of a carboxyl-terminal motif, KTEL, that is conserved from Xenopus to humans.…”
Section: Discussionmentioning
confidence: 99%
“…The AGR2 N terminus contains a sequence motif characteristic of signal peptides, which results in protein targeting to the secretory pathway of the cell. Indeed, several studies have proposed that AGR2 secretion from the cell is necessary for its action (7,10,14,16). In addition, yeast two-hybrid screens identified AGR2 binding proteins that naturally occur on the cell surface (9,22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These limbs can be transplanted to the flank of a normal larva, where they can regenerate in the absence of nerve supply (33). This lack of nerve dependence is made possible by the substitution of nerve-derived factors from ectodermal appendages, including epidermis and glands (33).…”
Section: Discussionmentioning
confidence: 99%
“…One candidate factor is anterior gradient, which is expressed in the developing aneurogenic limb but decreased after grafting and innervation. 35 A series of grafting and in vitro studies in the latter half of the 20th century implicated proliferating blastemal cells as a major target of the nerves. In 1977, Liversage & Globus showed that blastemas cultured in vitro proliferated only if they remained innervated by spinal cord implants, 36 while Goldhamer et al found that implantation of dorsal root ganglia into the blastemas of denervated limbs rescued cell cycling, although it did not increase cell cycling in fully-innervated blastemas.…”
Section: History Of Nerve Dependence Research In the Salamandermentioning
confidence: 99%